CHICKEN GAME APPROACH IN CONFLICT RESOLUTION FOR SUSTAINABLE INFRASTRUCTURE DEVELOPMENT INNOVATION - Arief Setiawan (Department of International Relations, Brawijaya University, 2018)
Conflict is a necessity. Despite being a necessity, the handling can be engineered through careful planning. Chicken game approach in a game theory is an analytical instrument that can be used to prevent the occurrence of conflicts without the need to avoid it. Conflict resolution is the next stage when the conflict occurs. Adequate conflict resolution will not only ease the conflict, but even could become an instrument of empowerment. Indonesia's infrastructure development experiences often cause a tension. Those experiences become the basis so that the similar events do not recur in the future. It is intended that innovation of sustainable infrastructure development is not impeded. In fact, it is expected to accelerate in order to achieve the national interest.Keywords: chicken game approach, conflict resolution, infrastructure development